Perwira Chronicles Foodies - Lawrenzier, Raffael; Mohd Yunus, Mohd Amin (Applied Information Technology And Computer Science, 2025)
The Perwira Chronicles Foodies is an interactive E-Recipe website. The purpose of developing this system is to solve the problem of the home cooker and chef in searching for a good recipe. There are many different websites with different recipes, making it difficult for users to find what they’re looking for. Some recipes exclude crucial details like ingredient lists, cooking times, and nutritional data. Here, the user will find a centralized hub organized by categories, offering comprehensive details with every recipe. Ingredient lists, step-by-step instructions, helpful tips, and even nutritional information ensure successful culinary ventures. After completion, the system will allow users to access a wide range of recipes across various categories. Additionally, users will have the opportunity to attempt these recipes, thereby enhancing their cooking skills. Therefore, this website also give you chance to explre the authentic and traditional flavors of your own food learning different cooking techniques and discover new ingredient. This website will not only benefit home cooks but also assist professional chefs in improving their culinary creations and expanding their own recipes.